Economic Growth and R&D: Empirical Firm-level Analysis of the UK and the US - Chan, Hou I (2011)
Information and Communication Technology has become a necessity in our daily life. This probably credited to innovation of scientists who has put much effort on research and development. Not only does R&D affect economic growth, but also it improves human‟s living standard. Therefore many economists aim to examine the relationship between R&D and economic growth. Some of them supported the positive relationship and suggested that the reversible relationship is another subject for investigation. This study intends to analyze the relationship between economic growth and R&D in the UK and the US during 2005-2010. Cobb-Douglas production function and binary logit regression were used to investigate in this issue in which industry, firm age and firm size are controlled variables. The sample included listed firms of the London Stock Exchange and the NASDAQ Stock Market. However, the findings showed a negative relationship in both directions. Unobservable factors such as financial crisis in 2007-2008 might be the main reason of this abnormal relationship. Validity of the study is violated by limitations: a) sample size, b) research horizon, c) generalization, d) adequacy of proxy, e) omitted variables. Nevertheless, the significance of the contribution of R&D to growth cannot be denied. Further investigation of this issue should consider a longer research horizon since R&D investment contains a high level of uncertainty.